Effects of crumb rubber at different sizes in asphalt mixtures on mechanical properties - A. K., Alakhali; F. M., Yahaya; M. A., Almalik (IOP Publishing Ltd, 2021)
High vehicles loads due to increasing the road users are one of the main issues affecting the asphalt pavement surface and its performance by resulting various problems such as fatigue cracking and other deformations due to road overloading caused by vehicles loads. The use of crumb rubber in asphalt pavements has attracted increasingly growing attention and become one of the factors that increase the strength of the pavement. Crumb rubber is used to improve asphalt binder properties and pavement performance since it contributes as an additive material in the structural applications and reducing the environmental problem. The main contribution and purpose of this research is to investigate the effectiveness of adding crumb rubber into the asphalt by using the wet method. There were two different amounts of crumb rubber content used in this study (2.5 % and 3.5 % of the overall asphalt mixture weight) and two different crumb rubber sizes (0.6 mm and 0.3 mm) that were examined in this study. In addition to this study, asphalt grade 60/70 penetration grade. The performance of the modified binder is comparatively evaluated with an unmodified binder to find the best modifier. The evaluation is done through conducting the comparison between results obtained from modified and unmodified asphalt samples using Marshall stability, flow and resilience modulus test. The results from this study shows crumb rubber is an efficient material to be used as an additive to asphalt binder since it contributes in better performance by increasing the strength and stiffness of pavement and can be used for future development.